Draft Annual Plan 2008-2009 Union Territory of Daman and Diu - Planning Commission (Planning Commission, 2008)
Diu District is near Una of Junagarh District in Gujarat State. It has three parts- (1) Diu island (2) Ghogla town on main land (3) Simor, situated is Gujarat at a distance of 25.kms from Diu. Nearest Railway Station is Delwada at a distance of 9 kms. from Diu. But important trains are linked with Veraval station which is 90 kms. from Diu.
Union Territory of Daman and Diu, Department of Planning and Statistics